QUANTITATIVE RESEARCH OF FACTORS (CONVENIENCE OF ACCESS AND GENDER) INFLUENCING THE FOOD STORE CHOICE IN NAGYKŐRÖS - Földi, Kata; Szakály, Zoltán; László, Beáta (Applied Studies in Agribusiness and Commerce, 2024)
The objective of the research is to analyze the food purchasing decisions of Hungarian customers depending on priority factors (convenience of access and gender) that impact the food store choice. To identify the characteristics of food shopping behaviour, we conducted a customer survey of 220 individuals in the city of Nagykőrös. The data collection was carried out using a standard questionnaire and an online survey on the Nagykőrös public life community social media portal, and by informing shoppers about the possibility to fill in the questionnaire in the Municipality’s posts. The sample can be considered representative based on the gender distribution of the primary food purchaser. During the analysis of the data, in addition to descriptive statistics, we utilized factor analysis to describe the mindset of the customers, and created segments based on the factors influencing the choice of store using cluster analysis. For the vast majority of consumers, the primary determinant in selecting a store is the affordable price level, regardless of how often they make purchases. When shopping on a daily basis, customers prioritize the store’s proximity to their residence, promotional discounts, and variety of products available. Men tend to value a relaxed ambiance and convenient parking, while women prioritize special deals and competitive prices when choosing their regular shopping location We have identified price sensitivity, accessibility, location, and atmosphere as key factors. Throughout our research, we have categorized customers into four distinct clusters: Action-oriented family members (36.1%), Conscious shopping family members (29.9%), Price-conscious seniors (20.6%), and Curious beginners (13.4%). A significant hurdle for Hungarian retail companies is to enhance the quantity of their loyal customers, which they can solely achieve by taking market share from their rivals (primarily other retail companies). Initially, they must determine whether their customer base favours their kind of store for everyday or bulk shopping. They must cater to the demands of their target customer base (potentially the clusters established by our research) in relation to the key factors influencing store selection and purchase frequency, in order to attain success in their business. We suggest utilizing the factors that influence store selection as segmentation criteria.